5PSQ-012 Impact of therapeutic patient education in the prevention and treatment of venous thromboembolism in patients with cancer. (March 2019) - Le Meur, L; Benzidia, I; Hij, A; Madelaine, I; Frere, C; Deville, L; Farge, D
Abstract : Background: Venous thromboembolism (VTE), including deep-vein thrombosis (DVT) and pulmonary embolism (PE), is a frequent and severe complication in cancer patients, which is the second leading cause of death in this population. International guidelines recommend a low-molecular weight heparin (LMWH)-based treatment during at least 3 months and until chemotherapy begins. The pharmacy and the internal medicine department have developed a patient education programme (PEP) dedicated to patients treated for cancer-associated thrombosis (CAT). Purpose: The objective of PEP is to increase adherence and compliance to long term-treatment, to strengthen the autonomy and to prevent or limit the recurrent VTE or bleeding complications. We describe our cohort of patients and the impact of the PEP programme. Material and methods: From 2014 to 2017, data were retrieved from the electronic patient files. A minimum number of sessions for each patient was set at three, allowing funding by our supervisory authorities. Characteristics of the patients, the number of PEP sessions, anticoagulant, recurrences and bleeding were collected. Results: In the programme, 48 patients were included. The main cancers represented were breast cancer (35%) and lung cancer (13%). Sixty per cent of cancers were metastatic at baseline, 44% of patients were diagnosed with DVT, 12% with catheter related-thrombosis and 44% with PE. Tinzaparin was prescribed in 86% of patients. The average number of sessions performed per patient was 3.5. Nearly 30% of patients did not have this minimum of three sessions, either because of death, treatment break or relay by another drug class. PEP sessions increased the self-injection rate from 40% to 67%, injections by another person from 9% to 12% and reduced the rate of injections by a nurse from 51% to 21%. Nearly 12% of patients had recurrent thrombosis under anticoagulant therapy. Only 4% of patients experienced a bleeding event. In more than 85% of cases, patients reported being observant. Conclusion: The programme fulfilled its objectives, including understanding, treatment adherence and allowing patients to be more independent with injections. This programme is the first to describe a cohort of patients treated for CAT and the result of a good collaboration between physicians, pharmacists and nurses. References and/or acknowledgements: No conflict of interest.